2015
DOI: 10.1111/jar.12190
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among a Cohort of Persons with an Intellectual Disability in New South Wales, Australia

Abstract: Our findings indicate excess mortality of people with an intellectual disability when compared to the general population. They also indicate that females with an intellectual disability have a higher relative mortality compared to female same-aged general population peers, and also males with an intellectual disability, a finding replicated in other similar cohort studies. For international comparison using the WHO standard population, our intellectual disability cohort (ages 5-69 years) had a mortality of 4.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 12 publications
8
67
0
Order By: Relevance
“…122 Regardless of these methodological differences, the gender relationship between ID and mortality is complex and warrants further investigation. 123 We found an elevated risk of mortality in adults with Down syndrome, which was approximately three times higher than that in adults with ID without Down syndrome. Mortality in people with Down syndrome has been widely studied.…”
Section: Mortalitymentioning
confidence: 87%
See 3 more Smart Citations
“…122 Regardless of these methodological differences, the gender relationship between ID and mortality is complex and warrants further investigation. 123 We found an elevated risk of mortality in adults with Down syndrome, which was approximately three times higher than that in adults with ID without Down syndrome. Mortality in people with Down syndrome has been widely studied.…”
Section: Mortalitymentioning
confidence: 87%
“…However, simply comparing overall mortality rates could hide any potential gender disparity, as men of a similar age in the general population may have a higher underlying mortality rate than women from being more likely to engage in higher-risk lifestyles or behaviours, a difference that may not exist within the population with ID. 124 Therefore, although more deaths are observed among adult men with ID in many studies, 82,122,123,125 when the authors' analyses compare observed mortality with expected deaths in their control populations, using SMRs, they observe much higher expected mortality for women with ID. For example, in the New South Wales study, 123 the authors reported a SMR of 4.26 for women versus a SMR of 2.52 for men, whereas the Leicestershire study 122 produced a similarly higher SMR for women (3.24) compared with men (2.28).…”
Section: Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…There is good evidence from various sources that the rate of all-cause mortality is higher in individuals with ID, 63,279,282 particularly due to excess deaths from respiratory disorders, neurological diseases, congenital abnormalities and accidents. Standardised mortality ratios (SMRs) of 2.28 (95% CI 2.02 to 2.56) for men with ID and 3.24 (95% CI 2.83 to 3.69) for women with ID, compared with the general population, reported in a 14-year study of individuals from the Leicester area 279 were applied to the other-cause mortality rates that were derived from the ONS data.…”
Section: Cancer Mortalitymentioning
confidence: 99%